Chinese martial arts from antiquity to the twenty-first century - Lorge, Peter Allan 1967- (Cambridge University Press, 2012)
"In the global world of the twenty-first century, martial arts are practiced for self-defense and sporting purposes only. However, for thousands of years, they were a central feature of military practice in China and essential for the smooth functioning of society. Individuals who were adept in using weapons were highly regarded, not simply as warriors but also as tacticians and performers. This book, which opens with an intriguing account of the very first female martial artist, charts the history of combat and fighting techniques in China from the Bronze Age to the present. This broad panorama affords fascinating glimpses into the transformation of martial skills, techniques, and weaponry against the background of Chinese history, the rise and fall of empires, their governments, and their armies. Quotations from literature and poetry, and the stories of individual warriors, infuse the narrative, offering personal reflections on prowess in the battlefield and techniques of engagement. This is an engaging and readable introduction to the authentic history of Chinese martial arts"--